Estudo dermatoscópico do melanoma extensivo superficial - Fernanda Marques Trindade (2016)
BACKGROUND: Dermoscopy increases sensitivity in melanomadiagnosis, leading to early detection and improving the prognosis. OBJECTIVE: To describe clinical and dermoscopic features of superficial spreading melanomas, and indentify the differences between melanomas in situ, and invasive melanomas with thickness < and > 1mm. METHODS: We retrospectively evaluated dermoscopicimages of 58 melanomas, grouped according to their thickness. Two experienced observers evaluated together the dermoscopic features. RESULTS: 24 melanomas in situ, 28 invasive melanomas with Breslow 1mm (0,50mm ± 0,22mm) and six with Breslow > 1mm (2,35mm ± 2,02mm) were evaluated. In situ melanomas were smaller than invasive ones. The most common dermoscopic features were assymmetry (84,5%), multiple colors (81,0%) and atypical network (79,3%).Nonspecific pattern was more common in melanoma in situ (p = 0,028) and atypical network was more common in invasive thin melanomas (p = 0,029). Invasive melanomas presented with a higher frequency multicomponent pattern (p = 0,026) and multiple colors (p = 0,019), and melanomas with Breslow > 1mm showed higher frequency of negative network (p = 0,018). CONCLUSIONS: Melanomas in early stages presented higher frequency of nonspecific pattern and atypical network, while invasive and thick tumors presented multicomponent pattern, multiple colors and negative network.